A Short Glossary of Metaphysics - SIMONS, PETER (Routledge, 2009)
NOTE: Many of the words in this glossary have everyday meanings which are different from these. We give only the more specialized philosophical meanings. JOHNSONIAN HEALTH WARNING: like all glossaries and dictionaries, not infallible and not complete, but an honest attempt to capture the senses of principal usages and occasionally to recommend some over others.
PUBLISHED
Keywords: Philosophy